Traductrices – chercheuses – autrices et l’entre-deux-langues : la spécificité canadienne - Joanna Warmuzińska-Rogóż (Romanica Wratislaviensia)
The article presents the specificity of translation in Canada, taking into account the important role of female translators who are often also researchers. The author aims to show the interpenetration of different activities: translation, research, theoretical reflection and translation practice. In addition, she draws attention to the important issue of choosing the direction of translation. These features are described on the example of a few important figures from the world of translation, including S. de Lotbinière-Harwood, A. Whitfield and L. Saint-Martin. Their achievements have many features in common: an indispensable combination of theory and practice, an important feminist background and an extended vision of translation perceived not only as a transfer, but also as a creative practice.